2019
DOI: 10.17061/phrp29121903
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care provider–focused interventions for improving outcomes for people with type 2 diabetes: a rapid review

Abstract: Objectives and importance of the study: The bulk of care for people with type 2 diabetes occurs in primary health care. This rapid review evaluated the effectiveness of primary health care provider-focused interventions in improving biochemical, clinical, psychological and health-related quality-of-life outcomes in people with type 2 diabetes. Methods: We searched Medline, Embase, All EBM Reviews, CINAHL, PsycINFO and grey literature focusing on the Organisation for Economic Cooperation and Development (OECD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Studies have shown that delivery of diabetes care through strong PHC has resulted in lower health costs, better health outcomes, higher satisfaction of people with diabetes, fewer hospitalization rate, and greater socioeconomic equity (32)(33)(34)(35). While the prevalence of diabetes and its impact on health and overall quality of life is high in Nepal, low institutional capacity of primary health care center, inadequate human resources for health, lack of resources/funding and priority for diabetes and other NCDs and poor intersectoral coordination are some key challenges to implementing programs for prevention and control of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that delivery of diabetes care through strong PHC has resulted in lower health costs, better health outcomes, higher satisfaction of people with diabetes, fewer hospitalization rate, and greater socioeconomic equity (32)(33)(34)(35). While the prevalence of diabetes and its impact on health and overall quality of life is high in Nepal, low institutional capacity of primary health care center, inadequate human resources for health, lack of resources/funding and priority for diabetes and other NCDs and poor intersectoral coordination are some key challenges to implementing programs for prevention and control of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Health care professionals (HCPs) remain the centre point of effective management of T2D [ 14 ]. Previous studies have reported weight loss and improved glycaemic control in individuals with T2D with the use of self-management digital and online delivered LC diet programs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%